Development of a Productive Disposition Skills Instrument for Elementary School Students - Khabibur Rohman; Turmudi Turmudi; Dasim Budimansyah; Ernawulan Syaodih (Jurnal Elementaria Edukasia, 2023)
Productive disposition is one of mathematical skill that is rarely discussed and researched in nowdays era. Even though this skill is as important as other math skills. This study aims to develop an instrument for measuring productive disposition skills for elementary school students. The research method used is research and development (R&D) with the stages of instrument development consisting of preliminary studies, design, validation, and trials. The research subjects consisted of 99 students in grades 4 and 5 in 4 elementary schools in East Java. For the sake of selection of respondents, purposive random sampling technique is used by the researcher. Furthermore, for data analysis, it used a descriptive quantitative approach. The results of the study show that the developed productive disposition skills measurement instrument is valid and reliable. The results of the reliability test showed a Cronbach's alpha coefficient of 0.85. The construct validity of the instrument has also been well tested through exploratory factor analysis and item response analysis. The instrument consists of 22 statements that measure productive disposition skills on 5 indicators namely enthusiasm, self-confidence, endurance, curiosity and willing to share. The implication of this research is that the developed productive disposition skills measurement instrument can be used as an evaluation tool in learning that focuses on developing productive dispositions in elementary school students.